2022
DOI: 10.1021/acscatal.2c05451
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand, Highly Tunable, and Selective 5-Hydroxymethylfurfural Hydrogenation to Furan Diols Enabled by Ni and Ni3Ga Alloy Catalysts

Abstract: Catalytic conversion of the biobased platform chemical 5hydroxymethylfurfural (HMF) into high-value-added products (e.g., diols) has attracted considerable attention, where controlling the products' selectivity is a crucial and challenging issue. Herein, a series of hydrotalcite-based Ni and Ni 3 Ga alloy catalysts were prepared for HMF hydrogenation into furan diols. By optimizing the loaded metal and reduction temperature, >99% BHMTHF and 95.6% BHMF yields were gained over Ni 1.5 Al-LDO-700 and Ni 1.5 GaAl-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It can be seen that in the absence of any loaded metals, only raw materials and blank carriers are added, resulting in no production of target products. When additional metals such as Cu, Ni, Pd, and other third metals were loaded on the Ru–Sn catalyst, 15 respectively, the conversion rate of PTA exceeded 95%, while the yield of CHDM depended on the metal composition of the catalyst. The results indicate the addition of a Pd catalyst exhibited the best performance.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that in the absence of any loaded metals, only raw materials and blank carriers are added, resulting in no production of target products. When additional metals such as Cu, Ni, Pd, and other third metals were loaded on the Ru–Sn catalyst, 15 respectively, the conversion rate of PTA exceeded 95%, while the yield of CHDM depended on the metal composition of the catalyst. The results indicate the addition of a Pd catalyst exhibited the best performance.…”
Section: Resultsmentioning
confidence: 99%
“…5 Recent research on the mechanism of HDO has focused primarily on model compounds, where the reaction pathways of the model compounds and the correlations between catalyst structure and HDO performance of model compounds have been examined. 6,7 Due to their structure comprising both a phenolic hydroxyl (C aryl −OH) and an ether bond (C aryl −OCH 3 ), lignin-derived phenols such as guaiacol and dihydroeugenol (DHE) have attracted considerable study. 8−10 In recent years, the major trend for catalysts for HDO of lignin derivatives has been the use of precious metals and transition metals supported on various supports.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the major trend for catalysts for HDO of lignin derivatives has been the use of precious metals and transition metals supported on various supports. , The majority of precious metal catalysts consist of palladium, , platinum, rhodium, and ruthenium. Nevertheless, taking into account the expense of precious metal catalysts, as inexpensive metals, transition metal catalysts have emerged as promising HDO catalysts. The transition metal sulfide catalysts, such as the NiMo sulfides and CoMo sulfides, show good activity for the hydrodeoxygenation of lignin-derived phenols. However, these transition metal sulfide catalysts are rapidly deactivated and may contaminate the product with sulfur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Also, the modification of solid catalysts by means of alloying or selective poisoning can modulate the product selectivity of hydrogenation of unsaturated compounds. 19 It is found that, in the hydrogen transfer reaction of 5-hydroxymethyl furfural, noble metals such as Pd, Ru, and Rh preferentially undergo furan ring saturation to generate tetrahydrofuran-based products. However, when the noble metal catalysts are deactivated by sulfur poisoning, they can only hydrogenate the CO double bond to produce dimethylfuran.…”
Section: Introductionmentioning
confidence: 99%